1996
DOI: 10.1159/000267969
|View full text |Cite
|
Sign up to set email alerts
|

Distributional Change of Alpha-Tocopherol in the Rat Lens with Age

Abstract: Concentration of α-tocopherol (α-Toc.) in the rat lens (1,4 and 12 months old) was determined in single lenticular layers using gas chromatography and mass spectrometry. The highest concentration of α-Toc. in lens was found in the nucleus, followed by the deeper anterior and deeper posterior cortices, the shallow anterior and shallow posterior cortices, and the equatorial region. The topographic α-Toc. distribution in the lens did not differ between lenses of 1-, 4- and 12-month-old rats. A significant decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Nagata et al . [ 38 ] have shown that the highest level of ␣ -tocopherol in 1-month-old rat lenses is in the nuclear region followed by the deeper anterior cortex, the shallow anterior cortex, the shallow posterior cortex, and the equatorial region and that the distribution pattern of ␣ -tocopherol is similar in 4-and 12-month-old rat lenses and the level of ␣ -tocopherol in the lens fractions of 4-and 12-month-old rats is as follows: nucleus Ͼ deeper posterior cortex Ͼ deeper anterior cortex м shallow posterior cortex Ͼ shallow anterior cortex м equator. This finding indicates that the distribution of vitamin E Vol.…”
Section: Distribution Of Vitamin E In Ocular Lensesmentioning
confidence: 99%
“…Nagata et al . [ 38 ] have shown that the highest level of ␣ -tocopherol in 1-month-old rat lenses is in the nuclear region followed by the deeper anterior cortex, the shallow anterior cortex, the shallow posterior cortex, and the equatorial region and that the distribution pattern of ␣ -tocopherol is similar in 4-and 12-month-old rat lenses and the level of ␣ -tocopherol in the lens fractions of 4-and 12-month-old rats is as follows: nucleus Ͼ deeper posterior cortex Ͼ deeper anterior cortex м shallow posterior cortex Ͼ shallow anterior cortex м equator. This finding indicates that the distribution of vitamin E Vol.…”
Section: Distribution Of Vitamin E In Ocular Lensesmentioning
confidence: 99%